A review on incidences of foodborne diseases and interventions for a better national food safety system in Malaysia - Salleh W.; Lani M.N.; Abdullah W.Z.W.; Chilek T.Z.T.; Hassan Z. (Malaysian Society of Applied Biology, 2024)
Indexed by Scopus